Non-equilibrium Grain Boundary Wetting in Cu–Ag Alloys Containing W Nanoparticles. Issue 1 (2nd January 2016) - Shu, Shipeng; Zhang, Xuan; Bellon, Pascal; Averback, Robert S.
Abstract : Adding nanoparticles to soft matter and liquids is known to provide remarkable control in the processing of novel materials. Here, we demonstrate a similar potential in crystalline solids. Specifically, we show that the addition of a high density of W nanoparticles dramatically alters the coarsening behavior of precipitate-hardened Cu–Ag alloys. First, the nanoparticles suppress precipitate growth, but far more surprisingly, they induce non-equilibrium Ag wetting layers on grain boundaries. This observation is explained using kinetic Monte Carlo simulations, which show that caging of Ag precipitates by the W nanoparticles suppresses their growth and drives the formation of wetting layers.